Reproductive and pregnancy health care for women with intellectual and developmental disabilities: A scoping review. Issue 3 (22nd January 2022) - Ransohoff, Jade I.; Sujin Kumar, Prisha; Flynn, David; Rubenstein, Eric
Abstract: Background: Women with intellectual and developmental disabilities face poorer reproductive and pregnancy outcomes partially due to health care inequity. Our objective was to conduct a scoping review of reproductive and pregnancy related health care among women with intellectual and developmental disabilities. Methods: We systematically reviewed three databases for keywords pertaining to pregnancy, reproductive health, and intellectual and developmental disabilities. Two reviewers screened abstracts and extracted full text. We synthesised included papers, identifying common themes. Results: Thirty‐six papers met review criteria. Women with intellectual and developmental disabilities had lower fertility rates and were less likely to receive adequate sexual education compared to peers. While most women received prenatal care, uptake was lower and received later than women without intellectual and developmental disabilities. Conclusions: Pregnancy‐related health care is often lacking for women with intellectual and developmental disabilities. There are gaps inhibiting our understanding which prevents action to reduce health disparities.